La syllabe et la découverte du sens dans l’énonciation : phonologie et langues en contact en FLE - Maria‑Luisa Fernandez‑Echevarria (Multilinguales)
How can deviant utterances produce a significant speech? A learners’ corpus answers the question. Indeed, some metrical syllabic distribution seems to operate effectively in communication act, in spite of the atypical syntactic constructions, multiple options utterances and observed repetitions. Various advertising, press and paremiology examples reflect this linguistic strategy: a binary syntax informs syllabification to justify the meaning conveyed by the discourse. Syllabic templates acquire then iconic typology allowing the interpretation of different speech utterances and making possible the phonological approach to discourse analyse.